Chemical composition, in situ rumen degradability, and in vitro digestibility of Tithonia diversifolia ecotypes of interest for ruminant feeding - La O, Oreste; Gonz?lez, H.; Castillo, Y.; Ruiz, O.; Estrada, A.; Rios, F.; Guti?rrez, E.; Bernal, H.; Valenciaga, Dayki; Castro, Beatriz I.; Hern?ndez, Yasmila (Cuban Journal of Agricultural Science, 2012)
An experimental sequence was performed with nine ecotypes of Tithonia diversifolia (3, 5, 6, 10, 13, 17, 23, 24, and 25) to determine chemical composition, in situ rumen effective degradability (ED) of dry matter (DM), and in vitro apparent and true digestibility of DM, OM, NDF, and ADF. Times of 6, 12, 36, 48, and 72 h were used for the degradability study. The kinetic performance was characterized by rise in the dynamics of DM disappearance, whereas the rumen effective DM degradability had values between 26.29 and 86.55 % for different rumen turnover constants. The fit of the data of in situ rumen degradability to the model proposed showed R2 superior to 0.89. In the ecotypes under study, the estimates of DM and OM apparent digestibility (IVDMAD and IVOMAD) kept values inferior to the true digestibility of both constituents (IVDMTD and IVOMTD). The values of IVDMAD were within the range from 72.25 to 79.77 %, and those of IVOMAD were from 57.71 to 66.20 %, as compared with the values of IVDMTD and IVOMTD, which ranged from 81.08 to 85.66 %, and from 65.27 to 70.22 % respectively. There were differences between each of the plant materials per indicator (P < 0.01, P < 0.001). The chemical composition analysis results of the in situ DM rumen degradability and the in vitro apparent and true digestibility of the DM, OM, NDF, and ADF of the ecotypes of T. diversifolia suggest their nutritional value. However, physiological studies are required to link the cut frequency, the level of inclusion of these ecotypes, the degree of utilization of the nutrients by the animal and the effect of some secondary metabolites on the physiological and productive responses of the plant. Key words: in situ rumen degradability, digestibility, chemical composition, T. diversifolia.